2022
DOI: 10.1111/jpm.12871
|View full text |Cite
|
Sign up to set email alerts
|

Quality of dying among elderly people diagnosed with dementia in nursing homes: A mixed methods study

Abstract: Accessible Summary What is known on the subject Nurses working at nursing homes can play a pivotal role in mental health as a high proportion of residents diagnosed with dementia are in these facilities. Many institutionalized residents diagnosed with dementia develop clinical complications and symptoms that reduce the quality of dying. A mixed‐methods approach can help nurses with the difficult task of assessing the quality of dying among these residents and identify inconsistencies that cannot be found usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
(121 reference statements)
2
0
0
Order By: Relevance
“…The analysis of the best and worst mean scores for items of both scales coincides with those of a study conducted on professionals, 34 which indicated that while care and symptom control are acceptable, communication about end‐of‐life issues and managing residents' end‐of‐life preferences are deficient aspects in nursing homes.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The analysis of the best and worst mean scores for items of both scales coincides with those of a study conducted on professionals, 34 which indicated that while care and symptom control are acceptable, communication about end‐of‐life issues and managing residents' end‐of‐life preferences are deficient aspects in nursing homes.…”
Section: Discussionsupporting
confidence: 71%
“…33 The original authors of the QoD-LTC and QoD-TLC-C scales argued that although physical symptoms are prevalent and may contribute to suffering at the end of life, these scales assessing psychosocial aspects of the quality of dying are associated more with social isolation, family burden, and loneliness than with pain or other prevalent symptoms at the end of life. The analysis of the best and worst mean scores for items of both scales coincides with those of a study conducted on professionals, 34 which indicated that while care and symptom control are acceptable, communication about end-of-life issues and managing residents' end-of-life preferences are deficient aspects in nursing homes.…”
Section: Discussionsupporting
confidence: 69%